The Construction of China's Ethnic Politicians on Legislative Powers in North Sumatera Province - Rudi Salam Sinaga Sinaga; Waluyo Handoko; Khairunnisah Lubis (Universitas Pancasakti Tegal, 2021)
This study departs from the general perception that some legislative candidates understand when campaigning in general elections promising to provide economic welfare to the community. The problem is how to bring economic welfare to the community when the governmental function is the executive's authority. This study aims to answer how the construction of ethnic minority politicians (ethnic Chinese) against the concept of legislative power. Through qualitative research methods, this study will answer research questions using deductive and interpretive data analysis. Data obtained through literature studies and interviews. The results of the research conducted show that Chinese ethnicity has constructed legislative power as a theoretical concept in the modern era but at the level of activity has a variant of skills in articulating.